Phthalate esters in main source water and drinking water of Zhejiang Province (China): Distribution and health risks. (27th August 2015) - Wang, Xiaofeng; Lou, Xiaoming; Zhang, Nianhua; Ding, Gangqiang; Chen, Zhijian; Xu, Peiwei; Wu, Lizhi; Cai, Jianmin; Han, Jianlong; Qiu, Xueting
Abstract To evaluate the distributions and health risks of phthalate esters in the main source water and corresponding drinking water of Zhejiang Province, the concentrations of 16 phthalate esters in water samples from 19 sites were measured from samples taken in the dry season and wet season. The concentration of the total phthalate ester congeners in source water ranged from 1.07 μg/L to 7.12 μg/L in the wet season, from 0.01 μg/L to 1.58 μg/L in the dry season, from 1.18 μg/L to 15.28 μg/L from drinking water in the wet season, and from 0.16 μg/L to 1.86 μg/L from drinking water in the dry season. Of the 16 phthalate esters, dimethyl phthalate, dibutyl phthalate, di‐(2‐ethyl‐hexyl) phthalate, di‐iso‐butyl phthalate, bis‐2‐n‐butoxyethyl phthalate, and dicyclohexyl phthalate were present in the samples analyzed, dominated by di‐iso‐butyl phthalate and di‐(2‐ethyl‐hexyl) phthalate. The concentrations of phthalate esters in the wet season were all relatively higher than those in the dry season, and the drinking water had higher concentrations of phthalate esters than source water. The phthalate ester congeners studied pose little health risk to nearby citizens. Environ Toxicol Chem 2015;34:2205–2212. © 2015 SETAC